Oral glucose tolerance testing as a complement to fasting plasma glucose in screening for type 2 diabetes: population-based cross-sectional analyses of 146 000 health examinations in Västerbotten, Sweden. Issue 6 (8th June 2022) - Rosén, Anna; Otten, Julia; Stomby, Andreas; Vallin, Simon; Wennberg, Patrik; Brunström, Mattias
Abstract : Objective: To assess the effect of adding an oral glucose tolerance test (OGTT) to fasting plasma glucose (FPG) in terms of detection of type 2 diabetes (T2D) and impaired glucose tolerance (IGT). Design: Retrospective analysis of serial cross-sectional screening study. Setting: Population-based health examinations within primary care in Västerbotten County, Sweden. Participants: Individuals aged 40- 50 and 60 years with participation from 1985 to 2017. Those with previously diagnosed diabetes and FPG≥7 mmol/L were excluded. Primary and secondary outcome measures: Prevalence of hyperglycaemia on the OGTT (IGT and T2D defined as 2-hour postload capillary plasma glucose of 8.9–12.1 mmol/L and ≥12.2 mmol/L, respectively). Analyses were further stratified by age, sex and risk factor burden to identify groups at high or low risk of IGT and T2D on testing. The numbers needed to screen (NNS) to prevent one case of T2D through detection and treatment of IGT was estimated, combining prevalence numbers with average progression rates and intervention effects from previous meta-analyses. Results: The prevalence of IGT ranged from 0.9% (95% CI 0.7% to 1.1%) to 29.6% (95% CI 27.4% to 31.7%), and the prevalence of T2D ranged from 0.06% (95% CI 0.02% to 0.11%) to 7.0% (95% CI 5.9% to 8.3%), depending strongly on age, sex and risk factor burden. The estimated NNS to prevent one case of T2D through detection and lifestyle treatment of IGT ranged from 1332 among 40-year-old men without risk factors, to 39 among 60-year-old women with all risk factors combined. Conclusions: The prevalence of hyperglycaemia on OGTT is highly dependent on age, sex and risk factor burden; OGTT should be applied selectively to high-risk groups to avoid unnecessary testing in the general population.